Extranjeros en la propia patria - Juan N. Seguín : los tejanos y las guerras de independencia de México y Texas - Kökény, Andrea (Acta Hispanica, 2011)
The paper analyses how the Mexican Texans (téjanos) related to the Mexican War ofIndependence, what role thy played in the borderland region, and why some of them decided to supportthe Anglo-American immigrants in their War of Independence against Mexico in 1836. The study isprimarily based on the results of American historiography and the memoirs and correspondence of one ofthe most influential and controversial téjanos, Juan Nepomuceno Seguin. He was an outspoken critic ofthe centralist policies of Santa Anna, the Mexican president and supported the Texans' demand formore self-government. He fought in the regular army of Texas against the Mexicans, and after gainingindependence was elected to the Senate of the new republic and twice won election as mayor of SanAntonio. Then, however, as thousands of American newcomers arrived in Texas, he gradually became„a foreigner in his native land" and was forced to leave his homeland andflee to Mexico.